Konflik Dalam Penerapan Hukum Pengelolaan Sumber Daya Alam Pertambangan Mineral Dan Batubara Tanpa Izin Pada Skala Kecil - Widyawati Boediningsih; Tjoe Kang Long (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Currently, illegal use of natural resources is rampant, especially among middle to lower class people, many of whom carry out mining activities without permits as a means of livelihood. Of course, carrying out mining activities without a permit/illegally is a criminal act in accordance with the provisions in Article 158 and Article 160 of the Mineral and Coal Law. However, efforts to enforce the law against illegal mining are a complex challenge for law enforcement agencies because the existence of illegal mining is related to social and economic issues faced by poor communities living around mining locations. In fact, many illegal miners report an improvement in their welfare as a result of illegal mining activities. This journal will conduct an analysis of the factors that cause the emergence of illegal mining, the impacts it causes, and policy solutions in dealing with illegal mining. Regarding the problems mentioned above, first, the factors driving illegal mining will be discussed, including regulatory issues, bureaucratic capacity in granting permits, lack of appropriate supervision, obstacles in law enforcement, and socio-economic aspects. The impacts of illegal mining will also be discussed, such as the impact on environmental damage, state revenues, and social conflicts that may arise. In the context of law enforcement, the application of utilitarianism policies and the use of punishment as a last resort will be reviewed. This journal will conclude by providing recommendations for law enforcement agencies to consider a persuasive approach to illegal miners, while the government carries out stricter guidance and supervision to turn illegal mining activities into legitimate activities.